'Chatting Shit' in the Jobcentre: Navigating Workfare Policy at the Street-Level. (June 2023) - Redman, Jamie
Since the mid-1980s, out-of-work benefit receipt in the UK has been increasingly governed by a 'workfarist' mesh of conditionality and activation policies. A wealth of research has found that conditionality and activation policies trigger a range of harmful outcomes for benefit claimants. However, this research largely ignores how claimants may struggle against these policies to eschew harmful outcomes. Drawing on longitudinal interviews with 15 young men, this article demonstrates how claimants can subvert policy implementation to prioritise their own needs and interests. It is concluded that claimant struggles against policy implementation most accurately reflect survival strategies and are predominantly rooted in the 'material nexus' of class-based inequalities in capitalist societies.